Surgical techniques influence local environment of injured spinal cord and cause various grafted cell survival and integration - Hou, Shaoping (J Neurosci Methods, 2017)
BACKGROUND: Cellular transplantation to repair a complete spinal cord injury (SCI) is tremendously challenging due to the adverse local milieu for graft survival and growth. Results from cell transplantation studies yield great variability, which may possibly be due to the surgical techniques employed to induce an SCI. In order to delineate the influence of surgery on such inconsistency, we compared lesion morphology and graft survival as well as integration from different lesion methodologies of SCI. NEW METHOD: Surgical techniques, including a traditional approach cut + microaspiration, and two new approaches, cut alone as well as crush, were employed to produce a complete SCI, respectively. Approximately half of the rats in each group received injury only, whereas the other half received grafts of fetal brainstem cells into the lesion gap. RESULTS: Eight weeks after injury with or without graft, histological analysis showed that the cut + microaspiration surgery resulted in larger lesion cavities and severe fibrotic scars surrounding the cavity, and cellular transplants rarely formed a tissue bridge to penetrate the barrier. In contrast, the majority of cases treated with cut alone or crush exhibited smaller cavities and less scarring; the grafts expanded and blended extensively with the host tissue, which often built continuous tissue bridging the rostral and caudal cords. COMPARISON WITH EXISTING METHODS: Scarring and cavitation were significantly reduced when microaspiration was avoided in SCI surgery, facilitating graft/host tissue fusion for signal transmission. CONCLUSION: The result suggests that microaspiration frequently causes severe scars and cavities, thus impeding graft survival and integration.